Preventing Wrongful Convictions: An Analysis of State Investigation Reforms - Norris, Robert J. (Criminal justice policy review, 2019)
As more innocents are exonerated and researchers learn more about the causes of wrongful convictions, criminal justice practices have been altered to reduce the number of erroneous convictions, although reforms have varied widely in scope and substance throughout the nation. In this article, we provide an analysis of state-level investigative reforms important to the production of wrongful convictions as of mid-2016. Specifically, we collect and describe reform efforts in three investigatory areas: eyewitness identification, forensics, and interrogations. We then discuss wrongful conviction reforms and the innocence movement more generally, focusing on the importance of continued research into wrongful convictions as a critical policy issue in criminal justice.